(x-9)(3x+5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-9=0

3x+5=0

Set the first factor equal to 0.

x-9=0

Add 9 to both sides of the equation.

x=9

x=9

Set the next factor equal to 0.

3x+5=0

Subtract 5 from both sides of the equation.

3x=-5

Divide each term by 3 and simplify.

Divide each term in 3x=-5 by 3.

3×3=-53

Cancel the common factor of 3.

Cancel the common factor.

3×3=-53

Divide x by 1.

x=-53

x=-53

Move the negative in front of the fraction.

x=-53

x=-53

x=-53

The final solution is all the values that make (x-9)(3x+5)=0 true.

x=9,-53

Solve using the Square Root Property (x-9)(3x+5)=0